A note on the asymptotic behavior of the distribution function of a general sequence - Farhadian, Reza; Jakimczuk, Rafael (Annales Mathematicae Silesianae, 2021)
The aim of this note is to study the distribution function of certain sequences of positive integers, including, for example, Bell numbers, factorials and primorials. In fact, we establish some general asymptotic formulas in this regard. We also prove some limits that connect these sequences with the number e. Furthermore, we present a generalization of the primorial.